Characterization of indicators of suicidal behavior in high sports performance in the school category in Granma (Original) (Revista científica Olimpia, 2020)
The present investigation was implemented with the objective of making a diagnosis of the characteristics and manifestations of suicidal behavior in adolescents of high performance of the EIDE Pedro Batista, in Granma, in the school category. For this, a cross-sectional, descriptive-correlational study was used, through a quantitative research design. The "Practical guide for the evaluation of suicidal risk in adolescence", prepared by Pérez (2000), was implemented. The results obtained show that of the 10 items presented by the instrument, 3 were those with the highest incidence and always among the cases identified as at risk of developing suicidal behaviors, coming from a broken home, history of learning and adaptive disorders, and obvious changes of behavior.
Keywords: diagnosis; suicidal behavior; adolescents; broken home; history disorders; behavior